Comparative analysis of isokinetic muscle function, anaerobic power, and physical fitness in male Taekwondo players based on body mass index standards - Minhyuk Park; Yonghyun Byun; Sangho Kim (Journal of Men's Health)
Background: Body mass index (BMI) significantly affects athletic performance among Taekwondo athletes. This study assessed the impact of BMI on isokinetic muscle function, anaerobic power and physical fitness among Taekwondo athletes. Methods: Forty-five Taekwondo athletes were divided equally into three BMI groups: normal weight (NWG), overweight (OWG) and obese (OG). Measurements were analyzed using one-way Analysis of Variance (ANOVA) with Scheffe’s post-hoc test for group comparisons. Results: Isokinetic assessments revealed that OWG and OG demonstrated significantly higher right (F = 7.517, p < 0.01) and left (F = 9.664, p < 0.001) extensor strength compared to NWG. Additionally, OG showed greater right flexor strength (F = 4.644, p < 0.05) than NWG, while NWG exhibited higher right flexor strength per body weight (F = 4.050, p < 0.05) than OWG. Anaerobic power measures indicated that OWG and OG outperformed NWG in peak power (F = 31.679, p < 0.001), average power (F = 31.977, p < 0.001) and total energy (F = 29.936, p < 0.001); notably, OWG achieved the highest peak power relative to body weight (F = 6.775, p < 0.01) and demonstrated a more significant peak drop (F = 3.614, p < 0.05). In physical fitness tests, OWG and OG showed superior back strength (F = 13.171, p < 0.001), while NWG outperformed OG in sit-ups (F = 7.275, p < 0.01) and recorded faster reaction times in whole-body reaction tests to both sound (F = 6.289, p < 0.01) and light (F = 3.825, p < 0.05). Conclusions: BMI influences strength and power in Taekwondo athletes, but its limitations must be considered, as it does not reflect muscle mass. Athletes categorized as overweight based on BMI may possess greater muscle-related strength but reduced speed and endurance. Therefore, balanced conditioning and body composition analysis are essential for effective training.